Salvage high-dose-rate interstitial brachytherapy for perineal recurrence of prostate cancer after surgery and radiotherapy: a case report - Vavassori, Andrea; Durante, Stefano; Augugliaro, Matteo; Comi, Stefania; Cambria, Raffaella; Cattani, Federica; Lazzari, Roberta; Matei, Deliu Victor; De Cobelli, Ottavio; Orecchia, Roberto; Jereczek-Fossa, Barbara (Journal of Contemporary Brachytherapy, 2020)
Perineal seeding of tumor cells from prostate cancer (PCa) is very rare, and no standard treatment exists for this atypical presentation with no evidence of distant metastases. Local excision or external beam radiotherapy are used as local salvage treatments for such perineal masses, including those occurring after biopsy, surgery, or interstitial brachytherapy. We report on a patient who presented no evidence of disease and no late urinary or gastrointestinal toxicities at 58 months after receiving high-dose-rate brachytherapy (HDR-BT) for perineal recurrence of PCa after radical prostatectomy and salvage external beam radiotherapy. To the best of our knowledge, this is the first case treated with HDR-BT in this scenario.